1. (2 х-1) (2 х +1) — (х-3) (х +1)=18 2. (2 х…

Тема в разделе "Алгебра", создана пользователем Nefertiti, 29 авг 2020.

  1. Nefertiti

    Nefertiti Мелюзга

    Регистрация:
    24 май 2015
    Сообщения:
    0
    Симпатии:
    0
    1. (2 х-1) (2 х +1) — (х-3) (х +1)=18 2. (2 х +3) (2 х-3) — (х-2) (х +1)=7
     
  2. Антон54

    Антон54 Мелюзга

    Регистрация:
    2 мар 2013
    Сообщения:
    0
    Симпатии:
    0
    1,4x^2-1-x^2-x+3x+3-15=03x^2+2x-13=0D=1-3*(-13)=40=2sqrt10x1=(-1+2sqrt10) /3x2=(-1-2sqrt10) /3
     

Поделиться этой страницей